2014
DOI: 10.1021/ac502727s
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Fucosylated Hemopexin and Complement Factor H in Plasma of Patients with Liver Disease

Abstract: Enhanced fucosylation has been suggested as a marker for serologic monitoring of liver disease and hepatocellular carcinoma (HCC). We present a workflow for quantitative site-specific analysis of fucosylation and apply it to a comparison of hemopexin (HPX) and complement factor H (CFH), two liver-secreted glycoproteins, in healthy individuals and patients with liver cirrhosis and HCC. Label-free LC-MS quantification of glycopeptides derived from these purified glycoproteins was performed on pooled samples (2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 52 publications
10
57
2
Order By: Relevance
“…Formations of Lewis type epitopes such as SLeX, LeX, or LeY were recently observed on liver secreted glycoproteins [1721], in addition to the well-known increase in core fucosylated α- fetoprotein in hepatocellular carcinoma [2224]. These alterations in the glycosylation of proteins were extensively studied in human tissues and especially in serum [13,15,2527]. Other described alterations of glycans include increased branching, sialylation, agalactosylated glycans or polylactosamine chains [16,28,29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Formations of Lewis type epitopes such as SLeX, LeX, or LeY were recently observed on liver secreted glycoproteins [1721], in addition to the well-known increase in core fucosylated α- fetoprotein in hepatocellular carcinoma [2224]. These alterations in the glycosylation of proteins were extensively studied in human tissues and especially in serum [13,15,2527]. Other described alterations of glycans include increased branching, sialylation, agalactosylated glycans or polylactosamine chains [16,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have recently shown that this workflow can be used for quantification of glycopeptides [13,25, 4346]. Collision induced dissociation of glycopeptides (CID) yields high intensity oxonium ions that originate from the glycans and less intense peptide-glycan or peptide fragments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several applications of multiple reaction monitoring (MRM)-based glycopeptide analysis from a variety of biological systems and diseases were lately published including the use of MRM-based serum glycoproteomics to study esophagus diseases (140), liver disease (141), and the immunoglobulin subclasses (134,142,143). Among other technical challenges unique to MRM-based glycopeptide detection and quantitation, one of the most important considerations is the selection of the precursor-product transitions being monitored.…”
Section: Ms Acquisition Strategies In Glycoproteomics-lc-ms/mentioning
confidence: 99%
“…For instance, Benicky et al evaluated the site-specific core fucosylation for hemopexin (HPX; a glycoprotein with five N-glycosylation sites) and complement factor H (CFH; a glycoprotein with nine Nglycosylation sites) in patients with liver cirrhosis and hepatocellular carcinoma (HCC) [57]. HPX and CFH were isolated from blood samples and subjected to trypsin digestion, followed by digestion with neuraminidase and then endoglycosidase F2 and F3 (Endo F2 and F3).…”
Section: Glycosite-specific Glycosylation Approachesmentioning
confidence: 99%